2014
DOI: 10.1590/0103-8478cr20120633
|View full text |Cite
|
Sign up to set email alerts
|

Telas agrícolas como subcobertura no cultivo de alface hidropônica

Abstract: RESUMO Este trabalho teve como objetivo avaliar o efeito de diferentes tipos de telas de sombreamento utilizadas como subcobertura no cultivo hidropônico de alface. Para isso, foi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
0
7
0
9
Order By: Relevance
“…Lettuce cultivated in tropical regions with silver, black and red mesh showed a net increase in the number of leaves and the leaf area index, and this effect was attributed to the lower temperature promoted by the three mesh (Sales, Barbosa Filho, Barbosa, Viana, & Freitas, 2014). The authors also verified a respective decrease of 4.7 °C and 3.6 °C in the average temperatures inside the environments when compared to the control environment (covered with transparent plastic), providing results that match those found in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Lettuce cultivated in tropical regions with silver, black and red mesh showed a net increase in the number of leaves and the leaf area index, and this effect was attributed to the lower temperature promoted by the three mesh (Sales, Barbosa Filho, Barbosa, Viana, & Freitas, 2014). The authors also verified a respective decrease of 4.7 °C and 3.6 °C in the average temperatures inside the environments when compared to the control environment (covered with transparent plastic), providing results that match those found in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Under this condition, plants had the photosynthetic process compromised, producing less dry mass (He et al, 2016). However, shading favored the reduction in air and soil temperature (Table 4), which provided for a more suitable environment for plant growth and development, considering that in high temperatures, the vegetative development of the culture is affected, due to the juvenile phase acceleration, moving prematurely to the reproductive phase with low dry mass accumulation (Sales et al, 2014). According to Taiz et al (2017), the high temperature affects the speed of chemical reactions and internal process for solutes transportation and, consequently, the normal development of the plants.…”
Section: Resultsmentioning
confidence: 99%
“…The adaptation to different environments of cultivation varies according to the genetic potential of each group or cultivar, being essential knowledge about the different shading conditions (Guerra et al, 2017). A few researchers have reported the effect of shading screens in lettuce crops, such as Fu et al (2012), Sales et al (2014) and Gonçalves et al (2017), as well as the behavior of different cultivars, as demonstrated by Guimarães et al (2011), Souza et al (2013) and Blind and Silva Filho (2015). However, studies involving simultaneously different shading levels and lettuce cultivars are scarce, mainly those involving different groups.…”
Section: Introductionmentioning
confidence: 99%
“…As telas vermelha 35% e branca/prata 20% apresentaram valores intermediários de temperatura do solo (Tabela 1). Sales et al (2014) verificaram que a tela vermelha, como subcobertura de uma estufa coberta com filme plástico, não reduziu a temperatura máxima média do ambiente, enquanto a tela prata reduziu, em 4,0ºC, a temperatura do interior da estufa.…”
Section: Resultsunclassified
“…No segundo ciclo de desenvolvimento, também foi observada a mesma tendência no tamanho das folhas. Isso porque plantas cultivadas sob telas de sombreamento apresentam aumento da área foliar para maior interceptação da luz (Espindola Junior et al, 2009;Oliveira et al, 2011;Otoni et al, 2012;Sales et al, 2014), enquanto plantas expostas ao sol apresentam menores áreas foliares, como defesa à transpiração e à elevação da temperatura (Niinemets & Fleck, 2002). Além disso, Ribeiro et al (2012) apontam que a qualidade e a intensidade da radiação que incide sobre as folhas das plantas também promovem modificações na espessura do mesófilo, dos tecidos vasculares, da epiderme, da cutícula, da densidade e das demais características estomáticas, para tolerância a essas condições.…”
Section: Resultsunclassified